2011
DOI: 10.3892/or.2011.1151
|View full text |Cite
|
Sign up to set email alerts
|

Expression of TGFß1 and its receptors is associated with biological features of ovarian cancer and sensitivity to paclitaxel/carboplatin

Abstract: Abstract. It has been suggested that expression of TGFß1 and its receptors [TGFß receptor type I (TßRI) and TGFß receptor type II (TßRII)] may play a key role in the proliferation and progression of epithelial ovarian cancer. We investigated the biological significance of TGFß1 and its receptors, as well as their association with the tumor response to paclitaxel (PTX) and carboplatin (CBDCA). We studied 24 patients with ovarian cancer, primary peritoneal cancer, or fallopian tube cancer who had undergone surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 27 publications
0
7
0
1
Order By: Relevance
“…Seven of these used reverse-transcriptase PCR (RT–PCR) of mRNA to determine gene expression, one used a different method of quantification, the RiboQuant Multi-Probe RNAse protection assay system (mRNA electrophoresis) (Komiyama et al , 2011). The data are summarised in Supplementary Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven of these used reverse-transcriptase PCR (RT–PCR) of mRNA to determine gene expression, one used a different method of quantification, the RiboQuant Multi-Probe RNAse protection assay system (mRNA electrophoresis) (Komiyama et al , 2011). The data are summarised in Supplementary Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…The data are summarised in Supplementary Table 2. Increased gene expression of IGF1R (An et al , 2009), insulin-like growth factor-2 promoter transcripts (Lu et al , 2006), vascular endothelial growth factor C (VEGF-C) (Sinn et al , 2009), SRA1 (Leoutsakou et al , 2006), transforming growth factor-beta 1 (TCGF β 1) (Komiyama et al , 2011), Coxsackie-adenovirus receptor isoforms (CAR3/7 CAR4/7) (Reimer et al , 2007) and lower gene expression of the RNAse III enzyme Drosher (Merritt et al , 2008) have all been found to be associated with suboptimal debulking. It is of note that the studies vary in genes investigated promoter transcripts and definitions of optimal and suboptimal debulking.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that TGF-β1 mRNA expression was significantly lower in tumors of patients who had optimal surgery than in patients with suboptimal surgery. TGF-β1 mRNA expression was also significantly lower in tumors with high sensitivity to chemotherapeutics than in those with low sensitivity [160]. …”
Section: Tgf-β In Solid Tumorsmentioning
confidence: 99%
“…Acts immune suppressive, increases proteolytic activity of cells, adhesion and directly stimulates angiogenesis 44 Inhibits the function of CD8 C cytotoxic T cells and Th1 cells Inhibits the development of M1 macrophages from monocytes and plays an indispensable role in tumor development and progression 45 TGFß1 mRNA expression is an indicator of tumor sensitivity to standard therapy that it can identify biologically aggressive and highly malignant tumors and can predict the prognosis of patients with ovarian cancer 46 Serum level of TGF-b1 has no diagnostic and prognostic role and is associated with sensitivity to standard chemotherapy in ovarian cancer patients 47 CCL-2 /MCP-1 One of the key chemokines that regulate migration and infiltration of monocytes, memory T cells, NKC and DC to sites of inflammation. Has both tumor growth-promoting as growth-inhibiting influences 48,49 Chemotherapy (paclitaxel-carboplatin) can upregulate CCL-2 expression 50 Elevated CCL-2 expression by ovarian cancer cells is reported to be associated both with a better chemotherapy (paclitaxelcisplatin) responses 51 as with chemotherapy resistance 52 CCL-2 levels in serum of ovarian cancer patients compared to healthy controls are both described to be lower 28,29 as higher 30,31 Higher levels are associated with advanced disease 30,31 …”
Section: Tgf-bmentioning
confidence: 99%